Penentuan Daya Jerap Karbon Aktif Dari Meranti Merah Terhadap Ion Fe(III) - Yusra, Arif; Yusnimar, Yusnimar; Drastinawati, Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Waste pollution of heavy metals in the waters continue to rise each year. this may endanger the survival of living creatures that are in the vicinity. One of contributor of the heavy metalwaste in the waters is the result of discharges of industrial waste. Activated carbon which has a high adsorption capacity for the adsorbate. Activated carbon can be produced from materials containing carbon or charcoal was treated in a certain way to gain more surface area. The purpose of this research was to determine the ability of activated carbon adsorption of the ion Fe (III) which in the synthesis of red meranti. This research used two methods of activation that chemical activation with activator concentration variation Na2CO3 4%, 5% and 6% w/v, and physical activation with temperature variation of 300 0C, 500 0C and 700 0C. The characterization of activated carbon which include: moisture content, ash content and adsorption capacity for iodine based Standard SNI 06-3730-95, and determining the ability of activated carbon jerap against ion Fe (III) at concentrations of 20 ppm. Theresults obtained by the characteristics of the activated carbon 06-3730-95 meet SNI standards. Adsorption capacity of active carbon on ion Fe(III) has maximal value at 99.745% physic way with temperature at 300 0CKeywords : Activation , Ion Fe (III), Activated Carbon